Dublin III and Beyond: Between Burden-sharing and Human Rights Protection - Dragan, Andrei (Pécs journal of international and European law, 2017)
The main purpose of this paper is to point out briefly the deficiencies of the present-day Dublin system and to outline one of the proposals that seeks to offer a solution that would make burden-sharing between the Member States possible and desirable and also protect human rights.